Advances and controversies in management of breast ductal carcinoma in situ (DCIS). Issue 4 (April 2022) - Farante, Gabriel; Toesca, Antonio; Magnoni, Francesca; Lissidini, Germana; Vila, José; Mastropasqua, Mauro; Viale, Giuseppe; Penco, Silvia; Cassano, Enrico; Lazzeroni, Matteo; Bonanni, Bernardo; Leonardi, Maria Cristina; et al.
Abstract: Ductal carcinoma in situ (DCIS) is a non-obligate precursor of invasive breast cancer. It accounts for 25% of all breast cancers diagnosed, as a result of the expansion of breast cancer screening and is associated with a high survival rate. DCIS is particularly clinically challenging, due to its heterogeneous pathological and biological traits and its management is continually evolving towards more personalized and less aggressive therapies. This article suggests evidence-based guidelines for proper DCIS clinical management, which should be discussed within a multidisciplinary team in order to propose the most suitable approach in clinical practice, taking into account recent scientific studies. Here we include updated multidisciplinary treatment protocols and techniques in accordance with the most recent contributions published on this topic in the peer-reviewed medical literature, and we outline future perspectives.